Nordic Walking for the Management of People With Parkinson Disease: A Systematic Review. Issue 11 (8th July 2017) - Cugusi, Lucia; Manca, Andrea; Dragone, Daniele; Deriu, Franca; Solla, Paolo; Secci, Claudio; Monticone, Marco; Mercuro, Giuseppe
Abstract: Background: It is well known that physical exercise is the main therapeutic element of rehabilitation programs for people with Parkinson disease (PD). As traditional forms of exercise can guarantee significant health benefits, the emergence of nonconventional physical activities, such as Nordic walking (NW), may add positive effects. Objective: To appraise the available evidence on the main effects of NW in the rehabilitation programs for people with PD and to propose a design for upcoming research that might improve the uniformity of future trials. Study Design: Systematic review. Literature Survey: A literature search of 5 established databases (PubMed, MEDLINE, Scopus, Web of Science, and Cochrane) was conducted. Methodology: Any relevant randomized controlled trials pertinent to NW in PD published in English from inception to February 2017 were included. Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines were followed, and the methodologic quality of each study was assessed by the Physiotherapy Evidence Database scale. Data Synthesis: Sixty‐six studies were retrieved, and 6 randomized controlled trials (221 subjects) were entered into the qualitative synthesis. Overall, these studies portrayed NW as feasible and likely to be effective in improving the functional and clinical outcomes of people with PD. When we compared NW with other exercise‐based interventions, such as treadmill training, free walking, a program of standardized whole‐body movements with maximal amplitude (Lee Silverman Voice Treatment BIG training), or a home‐based exercise program, the findings proved controversial. Conclusions: High heterogeneity and methodologic discrepancies among the studies prevent us from drawing firm conclusions on the effectiveness of NW in comparison with other exercise‐based interventions currently used by people with PD. Further investigations with a common design are necessary to verify whether NW may be included within conventional rehabilitation programs commonly recommended to people with PD. Level of Evidence: II